Comparative evaluation of changes in microflora in delayed and immediate implant placement: An In vivo study - Shivendra Choudhary; Neeraj Verma; Santosh Anand; Abhishek Sinha; Daya Shankar (Wolters Kluwer Medknow Publications, 2021)
Aim: This study is aimed to compare and evaluate the changes in the microflora in immediate and delayed placed implants. Materials and Methods: In this study, the implant site sample was taken and assessed during different phases of treatment for delayed and immediate implants. They were looked for Streptococcus, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Porphyromonas gingivalis, and Fusobacterium nucleatum. Results: The results showed that Streptococci were found in a higher number in all the phases of the treatment. The presence of pathogenic organisms such as P. gingivalis and Fusobacterium, in considerable amounts, was seen in both the groups. Conclusion: Thus, we conclude that implant mode of placement, delayed or immediate placement does not alter the flora of the oral cavity. Organisms present remains the same in all the phase of the treatment. To prevent the disease, one must continuously monitor the implant, with the increasing age changes, the microflora is continually changing in the oral cavity. The periodontal health should be assessed before the placement of the implant, followed by follow-ups after a set period for a better prognosis.